Disposition of Intravenous Pyrimethamine in Healthy Volunteers - Almond, D. S. (American Society for Microbiology, 2000)
A proportion of patients with AIDS and toxoplasmic encephalitis (TE) sustain low plasma pyrimethamine concentrations during oral treatment, possibly because of incomplete and variable bioavailability. We wanted to develop a safe, practicable intravenous (i.v.) formulation of pyrimethamine and characterize its disposition in healthy volunteers. A neutral, aqueous, sterile solution of pyrimethamine was produced and presented in sealed glass ampoules. Pyrimethamine (1 mg/kg) was given to eight healthy male volunteers by i.v. infusion over 2 h, and blood was sampled over a 2 week period. Pyrimethamine levels in plasma were measured by high-performance liquid chromatography. The drug was well tolerated by all volunteers, and there were no changes in vital signs, electrocardiogram, hematology, or biochemical parameters. The maximum pyrimethamine concentration of 2,089 ± 565 ng ml(−1) (mean ± standard deviation) was achieved shortly after the end of the infusion; thereafter, concentrations declined in a log-linear manner, with a half-life of 140 ± 31 h.